Uncovering Customer Orientation in Product Development - A Qualitative Study based on the Software Industry - Anantaraman,Sharmily; Hussein,Hibo (2015)
PURPOSE: The purpose of this research project is to further advance theory on management of product development by providing insights on customer orientations. The study contributes to the literature by bringing in Actor-Network Theory (ANT) as a new perspective to theorize the process of translations between customer orientation and engineering orientation within product development. RELEVANCE: Due to a mismatch in thinking between customer and development teams it is observed that it can be complicated for a product manager to help the development teams to perceive the product in terms of the customer usage. The inability of software development teams to incorporate customer perception into product development leads to unwanted delays and increased costs. METHODOLOGY: A qualitative research method was employed with an interpretive approach, using an abductive approach of reasoning. Eight face-to-face and electronic semi-structured interviews were conducted, utilizing hermeneutic analysis. FINDINGS: Our findings indicate that tensions between product development and customer orientation could be best confronted by stressing the use of technological artifacts as a medium of communication, and cross-functional management for translating customer orientation. The role of the PM as a mediator, collaborator and influencer is emphasized and crucial for negotiating a balance between a dominant engineering approach with customer orientation in product development. Knowledge visualization tools support the transfer of tacit knowledge and enable knowledge creation. CONTRIBUTIONS: Our contribution is an in depth understanding of the underlying tension that exist when incorporating customer perception in product development. We have endeavored to make sense of product management challenges in this respect.
Keywords: Product Manager; Product Development; Software; Knowledge Management; Actor-Network Theory; Customer-orientation and Product Management